A systematic literature review and meta-analysis of the effect of psilocybin and methylenedioxymethamphetamine on mental, behavioural or developmental disorders. (March 2023) - Kisely, Steve; Connor, Mark; Somogyi, Andrew A; Siskind, Dan
Objectives: There is an increasing interest in combining psilocybin or methylenedioxymethamphetamine with psychological support in treating psychiatric disorders. Although there have been several recent systematic reviews, study and participant numbers have been limited, and the field is rapidly evolving with the publication of more studies. We therefore conducted a systematic review of PubMed, MEDLINE, PsycINFO, the Cochrane Central Register of Controlled Trials, Embase, and CINAHL for randomised controlled trials of methylenedioxymethamphetamine and psilocybin with either inactive or active controls. Methods: Outcomes were psychiatric symptoms measured by standardised, validated and internationally recognised instruments at least 2 weeks following drug administration, Quality was independently assessed using the Cochrane risk of bias assessment tool and Grading of Recommendations Assessment, Development and Evaluation framework. Results: There were eight studies on methylenedioxymethamphetamine and six on psilocybin. Diagnoses included post-traumatic stress disorder, long-standing/treatment-resistant depression, obsessive-compulsive disorder, social anxiety in adults with autism, and anxiety or depression in life-threatening disease. The most information and strongest association was for the change in methylenedioxymethamphetamine scores compared to active controls in post-traumatic stress disorder ( k = 4; standardised mean difference = −0.86; 95% confidence interval = [−1.23, −0.50]; p < 0.0001). There were also small benefits for social anxiety in adults with autism. Psilocybin was superior to wait-list but not niacin (active control) in life-threatening disease anxiety or depression. It was equally as effective as escitalopram in long-standing depression for the primary study outcome and superior for most of the secondary outcomes in analyses uncorrected for multiple comparisons. Both agents were well tolerated in supervised trials. Trial quality varied with only small proportions of potential participants included in the randomised phase. Overall certainty of evidence was low or very low using the Grading of Recommendations Assessment, Development and Evaluation framework. Conclusion: Methylenedioxymethamphetamine and psilocybin may show promise in highly selected populations when administered in closely supervised settings and with intensive support.